Poster Presentations 2019
DOI: 10.1136/annrheumdis-2019-eular.491
|View full text |Cite
|
Sign up to set email alerts
|

Thu0191 upadacitinib as Monotherapy in Patients With Rheumatoid Arthritis: Results at 48 Weeks From the Select-Monotherapy Study

Abstract: BackgroundIn the SELECT-MONOTHERAPY trial, upadacitinib (UPA), an oral JAK1-selective inhibitor, showed efficacy when used as monotherapy over 14 weeks (wks) in rheumatoid arthritis (RA) patients (pts) with an inadequate response to methotrexate (MTX).1 ObjectivesSafety and efficacy of UPA monotherapy were assessed through 48 wks in an ongoing long-term extension period of SELECT-MONOTHERAPY.MethodsAt baseline (BL), pts on stable MTX were randomized to either continue MTX (cMTX, given as a blinded study drug) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…Upadacitinib 15 mg, as monotherapy or in combination with csDMARDs/methotrexate, met all primary and ranked secondary efficacy endpoints and achieved significantly higher remission and LDA rates than placebo, methotrexate, and adalimumab across all five pivotal phase III trials in the SELECT clinical program [25,29,48,49,54].…”
Section: Summary Of Benefit-risk Assessmentmentioning
confidence: 95%
“…Upadacitinib 15 mg, as monotherapy or in combination with csDMARDs/methotrexate, met all primary and ranked secondary efficacy endpoints and achieved significantly higher remission and LDA rates than placebo, methotrexate, and adalimumab across all five pivotal phase III trials in the SELECT clinical program [25,29,48,49,54].…”
Section: Summary Of Benefit-risk Assessmentmentioning
confidence: 95%
“…From 1,565 unique records, we identified 14 trials that met our inclusion criteria, involving 13,524 patients (Kremer et al, 2013;Fleischmann et al, 2015;Taylor et al, 2017;Burmester et al, 2018;Genovese et al, 2018;Fleischmann et al, 2019;Smolen et al, 2019;Rubbert-Roth et al, 2020;van Vollenhoven et al, 2020;Ozdede and Yazıcı, 2022). See Figure 1 for the PRISMA flow diagram summarizing search results.…”
Section: Search Results and Description Of Included Studiesmentioning
confidence: 99%
“…The flowchart of the literature selection is shown in Figure 1. Of 3,428 studies initially identified, a total of 44 citations including 47 distinct RCTs (Fleischmann et al, 2012;van Vollenhoven et al, 2012;Kremer et al, 2013;van der Heijde et al, 2013;Lee et al, 2014;Bachelez et al, 2015;Fleischmann et al, 2015;Keystone et al, 2015;Papp et al, 2015;Tanaka et al, 2015;Genovese et al, 2016a;Genovese et al, 2016b;Takeuchi et al, 2016;Abe et al, 2017;Dougados et al, 2017;Fleischmann et al, 2017;Gladman et al, 2017;Kavanaugh et al, 2017;Kivitz et al, 2017;Mease et al, 2017;Panés et al, 2017;Sandborn et al, 2017;Taylor et al, 2017;van der Heijde et al, 2017;Vermeire et al, 2017;Westhovens et al, 2017;Zhang et al, 2017;Burmester et al, 2018;Genovese et al, 2018;Mease et al, 2018;Genovese et al, 2019;Smolen et al, 2019;Takeuchi et al, 2019;van der Heijde et al, 2019;Deodhar et al, 2021;Feagan et al, 2021;McInnes et al, 2021;Mease et al, 2021;Chen et al, 2022;Danese et al, 2022;Deodhar et al, 2022;…”
Section: Search Strategy and Study Characteristicsmentioning
confidence: 99%